Main Tendencies and Modern Models of Educational Quality Management - Askarov Abror Davlatmirzayevich (Genius Publishing Group, 2022)
The article highlights the main trends in the quality management of education in the training of competitive personnel in a modern higher education institution and the improvement of pedagogical technologies of the modern model.
Keywords: Higher education; quality; globalization; strategy